Influence Factors on the Properties of Ultrahigh-Performance Fiber-Reinforced Concrete Cured under the Condition of Room Temperature - Pu Zhang; Yiliang Huang; Yongqi Li; Jun Zhao; Hengqian Dong; Tao Chen (Advances in Civil Engineering)
Ultrahigh-performance fiber-reinforced concrete (UHPFRC) is a new type of concrete with excellent performance and good application prospects. However, expensive heat curing or high-pressure curing was often adopted to ensure the sufficient compressive strength. This study focuses on improving the compressive strength and workability of UHPFRC by changing the composition materials and the mixture ratios under standard curing conditions. The 0-1 mm and 1∼3 mm sintered bauxite was adopted as coarse aggregate. UHPFRC with high compressive strength and good workability was developed by changing the water-binder ratios, by adding ground-granulated blast furnace slag (GGBFS) or fly ash, and by changing the bauxite content of different particle sizes. When the volume ratio of steel fiber was 3%, the recommend water to binder ratio was 0.194 according to this experiment, the dosage of GGBFS-replaced cement is recommended as 20%, the dosage of fly ash instead of silica fume is recommended as 30%. The recommend ratio of 0-1 mm and 1∼3 mm sintered bauxite was 1.51 : 1. Finally, a kind of UHPFRC material with a compressive strength of 152.4 MPa and a slump of 120 mm was developed under the standard curing conditions.